ACTOR SYNERGY AND PROGRAM CONVERGENCE: A MULTI-STAKEHOLDER COLLABORATION ANALYSIS IN POVERTY ALLEVIATION IN JAMBI PROVINCE - Subhan, Ahmad; Lestari, Linayati; Sejaya, Burlian (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
Poverty remains a strategic development issue in Indonesia, including in Jambi Province, which, despite a declining poverty and extreme poverty rate between 2020 and 2024, still faces spatial disparities and targeting inaccuracies. This study aims to analyze the implementation of the poverty reduction program convergence strategy in Jambi Province, emphasizing the role of multi-stakeholder collaboration. A descriptive qualitative approach was employed through a desk study based on data from Bappeda, BPS, and relevant academic literature. The analysis applies the theories of collaborative governance and policy networks to examine actor interactions in policy planning, implementation, and evaluation. The findings indicate that program convergence in Jambi involves various cross-sectoral interventions such as MSME assistance, education, health, and housing that contribute to poverty reduction. However, effectiveness remains constrained by data inaccuracies, institutional overlap, and weak coordination within policy networks. The established multi-stakeholder collaboration remains largely consultative and has not yet achieved genuine policy co-production. This study highlights the need to strengthen collaborative governance through integrated data management and equitable multi-stakeholder forums to enhance the effectiveness of regional poverty reduction policies.